Zinc anode with different binders for alkaline Zn-MnO2 battery - Erni Syazwani Maswan (Nanyang Technological University, 2020)
Electrochemical devices such as batteries acts as a major component in most appliances. The world of Science and Technology is moving rapidly today, which certainly motivates scientists for more discoveries to be made in improving certain devices to keep up-to-date with the technology. Most of the batteries produced today are good but some fail to meet or maintain the most important criteria such as maximum output and its longevity.